Larger oocyte cohorts maximize fresh IVF cycle birth rates and availability of surplus high-quality blastocysts for cryopreservation. Issue 5 (May 2019) - Connell, Matthew T.; Richter, Kevin S.; Devine, Kate; Hill, Micah J.; DeCherney, Alan H.; Doyle, Joseph O.; Tucker, Michael J.; Levy, Michael J.
Abstract: Research question: How does oocyte cohort size affect IVF treatment outcomes? Design: Retrospective cohort analysis of 10, 193 fresh autologous oocyte retrievals among good-prognosis patients <35 years from 2009 to 2015. The primary outcome was live birth from a fresh transfer; secondary outcomes included cumulative live birth potential from the retrieved cohort and frequency of severe ovarian hyperstimulation syndrome (OHSS). Results: Live birth per fresh transfer increased as the oocyte cohort increased up to 11–15 oocytes, then plateaued. Beyond 15 oocytes, live birth rates from fresh transfer did not decrease, even at the highest oocyte yields. When accounting for the availability of cryopreserved high-quality supernumerary blastocysts, the cumulative number of potential live births per retrieval continued to increase as oocyte yield increased. Rates of severe OHSS increased rapidly with increasing cohort size above 7–10 oocytes when final oocyte maturation was triggered with human chorionic gonadotrophin (HCG), up to nearly 7% of HCG-triggered retrievals of >25 oocytes, but when triggered with gonadotrophin-releasing hormone (GnRH) agonist the severe OHSS rate remained relatively low and stable at approximately 1% even among retrievals of the largest oocyte cohorts. Conclusions: Live birth rates per fresh embryo transfer are highest among cycles with retrieval of 11 or more oocytes. Larger cohorts are not associated with any decline in fresh transfer birth rates. Total potential births per retrieval continue to increase as the number of retrieved oocytes increases. Rates of OHSS remain relatively low after retrieval of large oocyte cohorts if final maturation is triggered with GnRH agonist rather than HCG.